THE INFLUENCE OF SERVICE QUALITIES AND PROMOTION FOR CUSTOMER SATISFACTION AT PT. INDONESIA AIR & OCEAN LOGWIN - Munarsih Munarsih; Rizky Syafputra (Yayasan Education and Social Center, 2022)
This study aims to determine how much influence the quality of service and promotion either partially or simultaneously on knowing the customers of PT. Logwin Air & Ocean Indonesia. The research method used is quantitative. The population in this study are respondents who still use the products/services provided by PT. Logwin Air & Ocean Indonesia. By using a sample of 85 respondents. Data collection techniques by means of observation, and questionnaires, and data analysis techniques are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, simple and multiple linear regression analysis, coefficient of determination analysis and hypothesis testing (ttest) and ( Ftest). The results of this study indicate the influence of Service Quality on customer satisfaction of PT. Logwin Air & Ocean Indonesia with partial test results (ttest) between Product Quality (X) and Purchase Decision (Y) shows the t value > t table 2,987 with a significance level of 0.000 where the value is smaller than 0.05. And there is the effect of promotion on customers at PT. Logwin Air & Ocean Indonesia with partial test results (t test) between Promotion (X2) and target (Y) shows t count > t table 8.474 with a significance level of 0.000 where the value is less than 0.05. results Based on the simultaneous test (F test) obtained the value of Farithmetic > Ftable. where the value is smaller than 0.05, which indicates that the quality of service and promotion simultaneously affect the customer satisfaction of PT. Logwin Air & Ocean Indonesia